Coping with early stage breast cancer: examining the influence of personality traits and interpersonal closeness - Saita, Emanuela; Acquati, Chiara; Kayser, Karen (Frontiers in Psychology, 2015)
The study examines the influence of personality traits and close relationships on the coping style of women with breast cancer. A sample of seventy-two Italian patients receiving treatment for early stage breast cancer was recruited. Participants completed questionnaires measuring personality traits (Interpersonal Adaptation Questionnaire), interpersonal closeness (Inclusion of the Other in the Self Scale), and adjustment to cancer (Mini-Mental Adjustment to Cancer Scale). We hypothesized that diverse personality traits and degrees of closeness contribute to determine the coping styles shown by participants. Multiple regression analyses were conducted for each of the five coping styles (Helplessness/Hopelessness, Anxious Preoccupation, Avoidance, Fatalism, and Fighting Spirit) using personality traits and interpersonal closeness variables (Strength of Support Relations, and Number of Support Relations) as predictors. Women who rated high on assertiveness and social anxiety were more likely to utilize active coping strategies (Fighting Spirit). Perceived strength of relationships was predictive of using an active coping style while the number of supportive relationships did not correlate with any of the coping styles. Implications for assessment of breast cancer patients at risk for negative adaptation to the illness and the development of psychosocial interventions are discussed.